Reference power values for the jump squat exercise in elite athletes: A multicenter study - Valenzuela, P. L.; McGuigan, M.; Sánchez-Martínez, G.; Torrontegi, E.; Vázquez-Carrión, J.; Montalvo, Z.; Abad, C. C. C.; Pereira, L. A.; Loturco, I. (Journal of Sports Sciences, 2020)
The present study aimed to provide reference values for lower-limb muscle power assessed during the incremental jump squat (JS) test in elite athletes (i.e., professional athletes competing at international level). We pooled data from all JS tests performed by elite athletes of different sports in two high-performance centres between 2015 and 2019, and computed reference values (i.e., terciles) for mean power (MP), mean propulsive power (MPP), and peak power (PP). Reference values were obtained from 684 elite athletes (458 male and 226 female) of 16 different sports (boxing, judo, karate, fencing, taekwondo, wrestling, basketball, soccer, futsal, handball, rugby union, badminton, tennis, long distance running, triathlon, and sprinting). Significant differences (p < 0.001) were found between male and female athletes for MP (7.47 ± 1.93 and 6.15 ± 1.68 W·K/, respectively), MPP (10.50 ± 2.75 and 8.63 ± 2.43 W/Kg), and PP (23.64 ± 6.12 and 19.35 ± 5.49 W/Kg). However, the velocity at which these power measures was attained seemed to be independent of sex (~0.95, 1.00 and 2.00 m·s-1 for mean, mean propulsive, and peak velocity, respectively) and homogeneous across different sport disciplines (coefficient of variation <10%). These data can be used to classify athletes` power capabilities, and the optimum velocity ranges provided here could be useful for training purposes.